STUDI KEANEKARAGAMAN, BIOMASSA DAN CARBON STOCK BAMBU DI TAMAN HUTAN RAYA K.G.P.A.A. MANGKUNAGORO I - Yus Andhini Bhekti Pertiwi; Malihatun Nufus; Ana Agustina; Rissa Rahmadwiati; Rezky Lasekti Wicaksono; Ike Nurjuita Nayasilana (Jurnal Belantara, 2021)
K.G.P.A.A. Mangkunagoro I Forest Park is the one and only forest park in Central Java. As area of protection, life support system, and biodiversity preservation, K.G.P.A.A. Mangkunagoro I Forest Park plays an important role for life, especially for people around the forest area. To ensure this function, the sustainability of forest functions is determined by the presence of vegetation in the forest area. The purpose of this study was to determine the diversity of species, biomass and carbon stock of bamboo in K.G.P.A.A. Mangkunagoro I Forest Park. The diversity of bamboo species was observed by exploration method with an inventory. Then, based on the inventory data obtained, one species of bamboo was selected based on its number of clumps to determine the biomass and carbon storage. In the present study, there were 20 species bamboo at K.G.P.A.A. Mangkunagoro I Forest Park namely Bambusa balcoa, B. balcoa var. Capensis, B. bambos, B. blumeana, B. multiplex-green hedge, B. multiplex-alphanse karr, B. oldhami, B. tuldoides, B. vulgaris vulgaris, B. vulgaris vitata, B. vulgaris wamin budha, Dendrocalmus asper, D. asper thai, D. asper black, D. hamiltoni, Guadua amplexifolia, G. agustifolia, Oxytenanthera abysinica, Phyllostacys aurea, dan P. nigra. Furthermore, D. asper (petung bamboo) was the most dominated bamboo species. The number of D. asper were 758 clumps/ha and 3,213 reeds/ha. The average D. asper biomass was 6.02 kg/reed. Thus, the estimated biomass per ha was 19.5 tonnes/ha. In addition, D. asper has the ability to store carbon of 9.1 tonnes/ha.